Beaded vessels - Goreski, Jeannine Denise, author; Lundberg, Thomas R., advisor; Williams, Ron G., committee member; Voss, Gary Wayne, committee member (Colorado State University. Libraries, 1988)
These vessels are full. They contain vastness, subtleties, memories, questions, and moments. These vessels are empty. They offer stillness and energy. Beads are vehicles. They connote the precious and command close inspection revealing structure, line, image, color, light, idea, and tactile sensuality. The intimate scale of the beads easily lends them to personal, passionate content. The center, crucial both structurally and philosophically is the genesis from which each vessel spirals upward and outward. Stitched together, each bead is locked in a structured, ordered brick system, pattern. This bead-by-bead building process is important; it speaks of time, frailty, vulnerability, and integral elements. Able to transmit light through matter, glass beads allow for emphasis through illumination. Light suggests seeing and entering. Notions of interior and exterior, knowing and darkness are addressed. Color, inseparable from light, symbolizes emotion. Form is dictated by metaphor. The spaces created are born of contemplation and inviting of contemplation. Symbols of growth, change, directions, motion, and transcendence reflect my thoughts and questions.
Zip file contains 20 slides of artist's works.
Keywords: Beadwork